Crossmodal face recognition - Casey, Sarah Jane (Trinity College (Dublin, Ireland). School of Psychology, 2006)
Although all faces share the same basic configuration of features, we are capable of distinguishing between, and recognising hundreds, and even thousands of faces with remarkable skill and precision. The perceptual processes, cognitive mechanisms, and neural substrates underpinning visual face recognition have been studied extensively. However, it is now acknowledged that the formation of coherent percepts of objects in the environment benefits from the merging of complementary sources of sensory information about that object. Therefore, researchers have been inspired to venture beyond vision, and examine how information from other sensory modalities can facilitate face recognition.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin